ANALISIS RASIO LIKUIDITAS DAN PROFITABILITAS PADA KINERJA KEUANGAN PT MARK DYNAMICS INDONESIA TBK YANG TERDAPAT DIBURSA EFEK INDONESIA (BEI) - Rahmawati, Nur; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze liquidity and profitability ratios on the financial performance of PT Mark Dynamics Indonesia Tbk for the period 2019–2023. The method used is descriptive analysis with a quantitative approach, using secondary data obtained from the company’s financial statements published on the Indonesia Stock Exchange (IDX).The variables analyzed include liquidity ratios (Current Ratio and Quick Ratio) and profitability ratios (Return on Assets and Return on Equity). The results indicate that the company’s liquidity condition is relatively stable, although fluctuations occurred during the COVID-19 pandemic. Profitability ratios showed a declining trend in 2020 but gradually improved in the following years.This study provides an overview of the company's financial performance based on financial ratios,. which can be used as a reference for investors and management in decision-making.